MULTI-STAKEHOLDERS GOVERNANCE IN SOCIAL SCIENCE DISCIPLINE: A SYSTEMATIC LITERATURE REVIEW - Taufik, Mohammad; Rahmat, Al Fauzi; Irawan, Bambang; Akbar, Paisal (Universitas Negeri Yogyakarta, 2021)
Multi-stakeholders governance (MSG) is a new governance design that involves many experts from multiple stakeholders to participate in dialogue, decision-finding (and possibly decision-making) and solution to common problem that occur. This article aims to analyze and identify topics on multi-stakeholder governance with a focus on social science disciplines. In particular, this article takes qualitative research with a literature study approach. The approach adopted in this paper consists of an initial selection of articles based on keywords of